(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
The removal of acidic components such as hydrogen sulfide (H₂S) and carbon dioxide (CO₂) from expander gas streams is essential for improving process efficiency and preventing equipment corrosion in gas processing industries. In this study, modified chemisorbents based on locally available bentonite were synthesized through chemical modification and thermal activation and evaluated for acid gas removal under low-temperature conditions. The modification significantly improved the structural properties of the sorbents, increasing the specific surface area from 62 to 176 m²/g and pore volume from 0.18 to 0.41 cm³/g. Sorption experiments showed that the H₂S adsorption capacity increased by approximately 3–4 times compared to natural bentonite, reaching 67 mg/g. Temperature studies confirmed the exothermic nature of adsorption, with optimal performance observed at 20–30°C. Dynamic column experiments demonstrated high sorbent efficiency and favorable mass transfer characteristics. The results indicate that modified sorbents derived from local raw materials are promising candidates for industrial purification of expander gas streams, offering potential advantages in cost reduction, operational efficiency, and environmental safety.